FISCAL FEDERALISM IN UNITED MEXICAN STATES - María Guadalupe Naranjo-Cantabrana (Ra Ximhai, 2017)
The purpose of this is to analyze the reason to be of the State, its elements, characteristics of Federal State, main differences between Federal States and Unit States; the constitutional framework and legality of fiscal federalism with respect to the federative entities, particularly Sinaloa. The bases of fiscal coordination are analyzed, considering the reforms of the fiscal coordination Law, published in the Official Diary of the Federation on July 18, 2016. The questions of this are: What is fiscal federalism? And, is there fiscal federalism in the United Mexican States? The Political Constitution of the United Mexican States and the Political Constitutions of the Federative Entities, the laws and other juridical norms that regulate the fiscal coordination between the Federation and the Federative Entities are precise. However, the subordination of the Federative Entities to the Federation is undeniable, the strengthening of the Federal Executive in the definition of public policies that impact the Federative Entities and Municipalities. The most important sources of public revenue are federal. The most important contribution of the country, between them the taxes, particularly income tax and value added tax are federal. Likewise, the rights for the use, enjoyment, use or exploitation of public domain assets contribute significantly in federal income. This makes them vulnerable to the Federative Entities since they depend their income of important way of the federal participations that are assigned to them.